Examination of paraben release from baby teethers through migration tests and GC–MS analysis using a stable isotope dilution assay - Theodoros Potouridis; Alena Knauz; Elisabeth Berger; Wilhelm Püttmann (BMC Chemistry, 2019)
Abstract Parabens and sorbic acid are commonly used as food preservatives due to their antimicrobial effect. However, their use in foods for infants and young children is not permitted in the European Union. Previous studies found these compounds in some gel-filled baby teethers, whereby parabens, which are well-known as endocrine disruptors, were identified in the polymer-based chewing surface consisting of ethylene-vinyl acetate (EVA). To assess the exposure of infants and young children to these products, the application of parabens in teethers should be thoroughly investigated. Therefore, the present study aimed to apply a representative migration test procedure combined with an accurate analytical method to examine gel-filled baby teethers without elaborate sample preparation, high costs, and long processing times. Accordingly, solid-phase extraction (SPE), in combination with a stable isotope dilution assay (SIDA) and subsequent gas chromatography–mass spectrometry (GC–MS) for analysis of methyl-, ethyl-, and n-propylparaben (MeP, EtP, and n-PrP), was found to be well-suited, with recoveries ranging from 93 to 99%. The study compared the release of these parabens from intact teether surfaces into water and saliva simulant under real-life conditions, with total amounts of detected parabens found to be in the range of 101–162 µg 100 mL−1 and 57–148 µg 100 mL−1, respectively. Furthermore, as a worst-case scenario, the release into water was examined using a long-term migration study.